Potential epidemiological impact of the 2017 American College of Cardiology/American Heart Association high blood pressure guideline on the Chinese population: a cross-sectional study in rural areas of Liaoning Province - Zhao Li; Guozhe Sun; Yingxian Sun; Zhaoqing Sun; Yue Dai; Jia Zheng; Yuanyuan Dong; Xiaofan Guo; Yanxia Xie; Yali Wang; Rongrong Guo; Liqiang Zheng (BMJ Open)
Objectives The present study estimated the percentage of rural Chinese adults with hypertension and recommended pharmacological antihypertensive treatment according to the 2017 American College of Cardiology/American Heart Association (ACC/AHA) guideline compared with the 2010 Chinese Guideline for the Management of Hypertension.Design Cross-sectional study.Setting Three counties in rural areas of northeastern China.Participants A total of 11 747 eligible individuals aged ≥35 years from rural areas of northeastern China were selected for the present analysis.Main outcome measures The percentage of rural Chinese adults with hypertension and recommended pharmacological antihypertensive treatment according to the 2017 ACC/AHA guideline and the 2010 Chinese Guideline for the Management of Hypertension, and the proportion of rural Chinese adults taking antihypertensive medication with blood pressure (BP) above the 2017 ACC/AHA guideline and the 2010 Chinese guideline treatment goal.Results The mean age of the study population was 53.9±10.8 years and 53.7% of the participants were women. According to the 2017 ACC/AHA guideline and the 2010 Chinese guideline, the crude prevalence of hypertension was 72.2% and 49.8%, respectively, and the percentage of recommended antihypertensive medications for rural Chinese adults was 56.4% and 51.4%, respectively. Among these rural Chinese adults taking antihypertensive medications, 96.7% had above goal BP according to the 2017 ACC/AHA guideline compared with 86.1% with above goal BP according to the 2010 Chinese guideline.Conclusion The present analysis demonstrated that compared with the 2010 Chinese guideline, the 2017 ACC/AHA hypertension guideline will result in a substantial increase in the percentage of rural Chinese adults defined as having hypertension and a small increase in the percentage of adults who are recommended antihypertensive medications. More intensive management is suggested to improve the control rate of hypertension among rural Chinese adults.